Metal-free degradation of methyl orange: unprecedented catalytic efficiency of rice husk-derived graphitic carbon - Kumkum Priyadarshini Sahu; Subhash Banerjee (Discover Materials)
Abstract Here, we report the fabrication of flake-like rice husk-derived chemically activated graphitic carbon (RCAGC) for metal-free degradation of MO under visible light conditions. RCAGC has been synthesised from biomass feedstock rice husk and characterized by Fourier transform infrared spectroscopy, powder X-ray diffraction, and field emission scanning electron microscopy. Flake-like RCAGC demonstrated remarkable efficiency in the degradation of MO, and 100% degradation of MO was achieved within 9 min of illumination under visible light. Moreover, real-time analysis of RCAGC-catalysed dye degradation was performed by the flow method using a column packed with an alternate layer of RCAGC and silica, followed by passing a solution of MO (20 ppm) through the column. A completely degraded colourless eluent was obtained, demonstrating the practical application of RCAGC material for the remediation of organic dyes in domestic water. The role of reactive species in the degradation was established by scavenger test, and it was observed that electron plays a crucial role in the degradation of MO under visible light.